Electric Vehicle Battery Optimization With Paper Batteries - Güvenilir, M.; Kozanoğlu, E.; Eren, A.; Aytekin, S. (Open Schools Journal for Open Science, 2021)
The rapidly developing study area of electric vehicles has taken a step further, especially with the new improvements in the battery systems of electric vehicles. Even though studies about this subject are still being conducted, a fully applicable solution has not yet been found. To tackle this problem, a supplementary battery pack formed by paper batteries will be implemented to assist the commonly used Li-Ion Battery(LIB) packs. In addition to this, suggestions to alter the battery cooling mechanism were explained as well. Consequently, with the use of paper batteries and the other solutions, the negative effects of ambient temperature, internal heating, and insufficient battery usage were diminished while increasing the range and efficiency of electric vehicles, and decreasing the carbon footprint.